248 Urethral Self-Insertion of a USB Cable as Sexual Experimentation: A Case Report. (28th February 2022) - Loufopoulos, I.; Kapriniotis, K.; Kennedy, C.; Huq, S.; Reid, T.; Sridhar, A.
Abstract: Introduction: The insertion of a foreign body in the urethra is an uncommon urological emergency. A wide variety of inserted objects have been described, presenting either asymptomatically or with lower abdominal discomfort and lower urinary tract symptoms. Sexual experimentation and gratification as well as mental disorders are considered the main underlying causes. The aim of this report is to present the case of a USB wire self-insertion and its challenging urological management. Case Presentation: A 15-year-old male patient presented to his local Accident and Emergency department with gross haematuria following self-insertion of the knotted cable of a USB wire into his urethra in the context of sexual experimentation. Endoscopic approach via rigid cystoscopy and optical urethrotomy was not effective. A suprapubic catheter was inserted, and the patient was urgently transferred to our hospital for tertiary management. Following radiological assessment to confirm the position of the wire, a longitudinal peno-scrotal incision over the palpable foreign body was made. Urethrotomy revealed the knotted cable in the proximal aspect of the penile urethra, which was cut and removed. Urethra was subsequently closed over a urethral catheter. Postoperative recovery was uneventful, and patient was discharged home with oral antibiotics. Urethral catheter was removed following normal fluoroscopic assessment of the urethra two weeks later. Conclusions: The management of a foreign urethral body can be challenging and usually requires tertiary expertise to achieve optimal outcomes. Poor initial management could potentially lead to devastating long-term complications such as urethral strictures and fistulas.